The History of Japan : giving an account of the ancient and present state and government of that empire . / Imperium Japonicum in sexaginta et octo provincias divisum : ex ipsorum Japonensium mappis & observationibus Kaempferianis, qua fieri licuit fide & cura descriptum - Scheuchzer, John Gaspar ([printed for the translator], 1727)
a Joh. Casparo Scheuchzer Nullmeridian ca. 11° westl. Ferro Namen der Provinzen lat. und japan. beschriftet 2 Nebenkarten (Kamtschatka; Tsugaro-Strasse) 2 Tabellen und div. Abb.